2011
DOI: 10.1002/adfm.201101047
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Structural Stability and Performance Durability of Bulk Heterojunction Photovoltaic Devices Incorporating Metallic Nanoparticles

Abstract: Despite the progress on organic photovoltaic (OPV) performance, the photoactive layer degradation during prolonged solar illumination is still a major obstacle. In this work, an approach to mitigate the degradation pathway related to structural/morphological changes of the photoactive layer occurring upon continuous illumination in air is presented. It is shown, for the first time, that the incorporation of Ag nanoparticles in poly(3‐hexylthiophene) (P3HT) and [6‐6]‐phenyl‐C61‐butyric acid methyl ester bulk he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 36 publications
(47 reference statements)
1
76
0
Order By: Relevance
“…Nonetheless, all these issues may be resolvable through a prudent choice of the constituents and careful optimization of the device. From the analysis of our experimental results and careful comparison with the literature reports [8][9][10][11][12][13] , we can identify several key factors/ considerations for the design of hybrid plasmonic OSCs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonetheless, all these issues may be resolvable through a prudent choice of the constituents and careful optimization of the device. From the analysis of our experimental results and careful comparison with the literature reports [8][9][10][11][12][13] , we can identify several key factors/ considerations for the design of hybrid plasmonic OSCs.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, metallic nanoparticles (NPs) have been commonly employed as subwavelength antennas and scattering centres to enhance the absorption of BHJ films 3 . Typically, these metal NPs are either embedded in the charge transfer layer such as PEDOT:PSS [4][5][6][7] or simply blended within the active BHJ layer [8][9][10][11] . In the latter approach, NPs coated with organic ligands are typically used to disperse the particles within the organic blends.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Furthermore recent studies demonstrated that the NPs can lead to an enhancement of the OPV device structural stability as well. [10][11][12] Methods to synthesize and incorporate MNPs are in abundance. Chemical synthesis can give precise control of size, however, it produces a lot of hazardour wastes, 13,14 with a requirement of an additional process step for deposition.…”
mentioning
confidence: 99%
“…As such, future studies should primarily foster materials development of new absorbers with enhanced photo and structural stability as well as alternative electron transport layers that are not subject to the requirement of photodoping. [51][52][53][54] Moreover, fully solution processed tandem OPVs on exible plastics with state-of-the-art encapsulation need to be demonstrated for certifying market readiness.…”
Section: Resultsmentioning
confidence: 99%